Posterior Reversible Encephalopathy Syndrome in a child after Severe Traumatic Brain Injury - Kumar Shrestha, Saurav; Subedi, Shradha; Shekhar Bhagat , Chandra; Singh Danuwar , Sunil; Tamrakar, Karuna (Eastern Green Neurosurgery, 2024)
Pediatric brain is anatomically and physiologically different from adult brain. Child’s brain is more vulnerable to the effects of a brain injury and takes longer to recover. Because the child’s brain is still developing, injury may alter the course of development of the brain and its functions. The child’s brain is less "set" than the adult’s, its plasticity offers hope to damaged tissue and areas. It is very rare to have posterior reversible encephalopathy syndrome as a complication of traumatic brain injury in children.